Integrasi keterampilan abad 21 (4C) dalam pembelajaran PAI: Strategi guru dalam membangun karakter adaptif dan religius - Mubarokah, Syifa Fatihatul; Hermawan, Wawan; Budiyanti, Nurti (Program Studi Magister Pendidikan Agama Islam, 2026)
Moral degradation and ethical erosion in the digital era necessitate a realignment between technical competence and spiritual maturity in education. This study aims to analyze strategies for integrating 21st-century skills (the 4Cs: Critical Thinking, Creativity, Collaboration, and Communication) into Islamic Religious Education (PAI) to foster student character that is adaptive yet deeply religious. Employing a descriptive qualitative design with a case study approach, this research involved three PAI teachers at a State Junior High School in Bandung. Data were collected through in-depth interviews and document analysis of Deep Learning-based teaching modules, then analyzed using thematic and content analysis techniques. The findings reveal the phenomenon of